Incorporation Level of Health Concepts in Social Studies Textbooks in the Primary Education Stage in the State of Qatar - Manal Hendawi (Deanship of Scientific Research (DSR), the University of Jordan, 2024)
Objectives: This study aims to identify health concepts in social studies textbooks for grades four to six in primary school and assess the distribution and proportion of these concepts in relation to the overall textbook area. Methods: Employing a descriptive analytical approach, a list of health concepts was compiled and categorized into four main areas within social studies textbooks in Qatar's primary education stage. Tool validity was confirmed through expert review, and to ensure analysis stability, a study unit was analyzed by the researcher and another curriculum specialist using the Cooper equation, resulting in an 84.5% analysis stability. Results: Environmental health concepts had the highest frequency (213), while concepts related to "diseases and health problems" had the lowest (5). Examining frequencies by grade, the fourth grade had the highest repetitions (125), followed by the fifth grade, second semester (96), and the sixth grade, first semester, had the lowest repetitions (37). Regarding the area of health concepts by grade, the fourth grade occupied the highest area (9.61) pages, while the sixth grade had the smallest area (2.84). Conclusions: The study revealed that the fourth grade had the highest frequency and allocated space for health concepts, whereas the sixth grade ranked the lowest. This suggests a deliberate emphasis on depth and breadth in the early stages of the curriculum to solidify information, gradually decreasing in subsequent grades.